Tren Transformasi Pendidikan Ekonomi Terhadap Investasi Pendidikan Berkelanjutan Sebagai Penguatan Sumber Daya Manusia Tahun 2016-2025 - Devangga Putra Adhitya Pratama; Priyo Utomo (Dharma Ekonomi, 2024)
This study analyzes the transformation of economic education towards educational investment as a means of strengthening human resources (HR) through a bibliometric approach. By utilizing Scopus basic data and the VOSviewer analysis tool, the study examines the trends in publications over the past ten years, focusing on key areas such as educational economics, educational investment, and HR development. The findings highlight that innovations in educational economics, including the integration of digital technology, project-based learning, and collaborations between educational institutions, government, and industry, are crucial in enhancing the effectiveness of educational investments. Additionally, the study reveals that the proper allocation of educational funds for infrastructure development, improving teaching quality, and implementing skills-based training programs significantly contributes to increasing workforce competitiveness and promoting sustainable economic growth. The research emphasizes that educational investment strategies must be aligned with the needs of industry and global challenges to foster adaptive and innovative human resources. Moreover, it stresses the importance of designing educational policies that are comprehensive, addressing the aspirations of individuals and the relevance of education to the labor market. Ultimately, the study offers valuable academic insights and practical recommendations for policymakers, educational institutions, and other stakeholders. It also provides guidance for developing effective strategies that optimize educational investment and support the cultivation of superior HR capable of driving future economic progress.